ANALISIS NILAI WAJAR SAHAM PUBLIK DALAM TENDER OFFER (Studi Kasus PT Bentoel Internasional Investama Tbk) - Herlitah Herlitah (Jurnal Ilmiah Econosains, 2014)
ABSTRACTThe purpose of this research is to analyze Fair Value of the stock price of PT Bentoel Internasional Investama Tbk. for tender offer after the acquisition from British American Tobacco. The Discounted Cash Flow/DCF Method of the Income Approach used for calculation within the Free Cash Flow to The Equity/FCFE Model.Keywords: Fair Value, Tender Offer, Income Approach, Discounted Cash Flow, Free Cash Flow to Firm.